LOVE AND HATE DEPICTED IN “THE MOTHER” SHORT STORY BY WILLIAM SOMERSET MAUGHAM - Roswita M. Aboe; Rohania Wati Buru (FKIP Universitas Khairun, 2021)
This research focuses on the analysis of love and hate in the short story “The Mother” by W. Somerset Maugham. The problem question is: How does the author describe love and hate in this novel. The focus of this research is about love and hate and elements of literature that are built in short stories. As a literary work, this analysis uses a descriptive research design that is used to describe the data based on the findings obtained in statements related to love and hate in short stories. The main data is the short story